The Maintenance Of Baung Fish (Hemibagrusnemurus) With Different Stocking Densities In Aquaponic Circulation Systems And Addition Of Probiotics In Feed - Zuria, Ridha; M Tang, Usman; Putra, Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT          This research was conducted from February to April 2019, for 45 days in Breeding Laboratory Unit of Fisheries Faculty and Marine Sciences,University of Riau Pekanbaru. The purpose of this research was to determine the optimal amount of stocking density in the maintenance of baung fish that was maintained with an aquaponic recirculation system and the addition of probiotics to the feed. The method used in this research was an experimental method with a one-factor completely randomized design (CRD) with 5 treatment levels and 3 replications, so that 15 experimental units were needed.The stocking density of baung used in this research is as follows: P1) 400 head/m3; P2) 500 head/m3; P3) 600 head/m3; P4) 700 head/m3; P5) 800 head/m3. The best treatment was obtained from P3, with a stocking density of 600 head/m3with absolute weight value of 6.18 g, absolute length of 4.89 cm, specific growth rate of 3.47, feed efficiency 98.91% and survival rate 93.06% . Water quality during the research was temperature 26-280C, pH 6.0-7.3, dissolved oxygen 4.3-7.0 mg/L and ammonia 0.01-0.21 mg/L. Keyword: Hemibagrus nemurus, Stocking density, Aquaponic recirculation, Probiotic